High affinity streptococcal binding to human fibronectin requires specific recognition of sequential F1 modules. - Schwarz-Linek, U; Pilka, E; Pickford, A; Kim, J; Höök, M; Campbell, I; Potts, JR (2004)
Fibronectin (Fn) binding by the Streptococcus pyogenes protein SfbI has been shown to trigger integrin-dependent internalization of this pathogen by human epithelial and endothelial cells. Here, using nuclear magnetic resonance spectroscopy and isothermal titration calorimetry in a dissection approach, the basis for the specificity and high affinity of the interaction between the N-terminal domain of Fn and SfbI is revealed. Each of the five Fn type 1 modules is directly involved in the interaction and is recognized by short consecutive motifs within the repeat region of SfbI. Crucially, these motifs must be combined in the correct order to form a high affinity ligand for the N-terminal domain of Fn.